UPAYA MEMINIMALISASI CACAT PRODUK DENGAN IMPLEMENTASI METODE LEAN SIX SIGMAS: STUDI KASUS PERUSAHAAN PT XYZ - Rhema Chintya Lestari; Kristina Fitri Handayani; Gun Gun Firmansah; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
Competition in the manufacturing industry is now very fierce. The growth of the industry is running rapidly and that is why competition in each industry is so fierce. PT XYZ is a glassware factory and produces glass tools produced through several stages of the process. Currently the company's capabilities cannot meet market demand. This causes backorders to occur almost every month. This inability is due to the large number of defective products (defects) and waste (waste). This allows the company to continue to manage existing production systems effectively and efficiently. Implementation of lean six sigma in identifying defects and waste. Fixed defects and reduced drilling to increase production output. Stream mapping is used for identification against waste. While the identification of defects is done by control charts. After obtaining the data and analyzed using the cause effect diagram and pareto diagram so as to produce a series of recommendations for system improvement. The results of the research obtained by analyzing the root cause analysis method is that the cause of defective products is in the process of machine preparation and the inaccuracy of the operator tuning the machine. While the cause of waste occurs due to breakdown in the machine used in the production process.